Acute Inferior Wall Myocardial Infarction due to Occlusion of the Wrapped Left Anterior Descending Coronary Artery. (24th July 2013) - Sunil Roy, Thottuvelil Narayanan; Nagham, Jafar Saeed; Anil Kumar, Rajappan
Abstract : Acute occlusion of the left anterior descending coronary artery (LAD) generally results in ST segment elevations in precordial leads and reciprocal ST segment depression in inferior leads. The occurrence of isolated inferior myocardial infarction due to occlusion of LAD is very rare. We describe an isolated acute inferior myocardial infarction due to occlusion of a wrapped LAD at the apex which continues as the large posterior descending coronary artery (PDA) beyond the occlusion.